Trade Union Organising in Private Sector Services : Findings from the British, Dutch and German retail industry - Heiner Dribbusch (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2005)
The aim of the paper is to take a closer look behind the curtain of low aggregate trade union densities in retail and to outline the major obstacles and problems trade union organising faces in the retail trades. Trade union organising and recruitment is analysed against the background of a 'two hurdle model of organising' (cf. Haas 2000, Dribbusch 2003) derived from explanations on trade union membership put forward by Green (1990) and Disney (1990). Within this framework the first hurdle to be taken is the establishment of a workplace presence as a precondition for any sustainable membership development. The second hurdle is then to convince the potential members in the workplace to join i.e. the recruitment.
Keywords: 330